THE EFFECT OF DESUGGESTOPEDIA ON THE WRITING COMPETENCE OF THE SECOND SEMESTER STUDENTS WITH DIFFERENT TEMPERAMENT, OF FKIP UNMAS DENPASAR - I.G.B, Oka Pramarta,; ., Padmadewi; W, SUARNAJAYA, (Universitas Pendidikan Ganesha, 2013)
Abstract This study aims at investigating the effect of desuggestopedia on writing competence of the second semester students with different temperaments, of FKIP UNMAS Denpasar. The problems of this study were formulated into two major points: 1) the effect of desuggestopedia on students? writing competence, 2) interaction between desuggestopedia and the temperament. This study was designed with experimental research and instruments being used were lesson plans, posttest, writing rubric, and questionnaire. It used intact random sampling which is one type of probability sampling technique. As a result, two classes from seven classes were chosen, one as the experimental group and the other as the control group. The research instruments used to obtain the data in this research were in the form of tests which were analyzed using descriptive analysis and Statistical Two-Way ANOVA. There were 2 findings in this research: 1) there was significant different effect on students? writing competence between the students who were taught by using Desuggestopedia and those who were taught by conventional technique, 2) there was not significant interaction effect between desuggestopedia and students? temperament on students? writing competence. Keywords : writing, desuggestopedia, sanguine, melancholic